Peranan Crewing Department terhadap Pengadaan Crew Kapal pada PT. Margo Indonesia Servicestama Jakarta - Lupita Rahel Simanjuntak; Yusnidah Yusnidah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to analyze the vital role of the Crewing Department in the recruitment, placement, and management of ship crew members at PT Margo Indonesia Servicestama Jakarta. The availability of competent, loyal, and ethical crew members is a key factor for ensuring the safety and efficiency of shipping operations. This study focuses on the procedures and strategies implemented by the crewing department to guarantee that recruited personnel meet company standards, uphold core values, and demonstrate a strong work ethic. The research employs field research to directly observe recruitment and crew placement practices, complemented by a literature review to examine relevant regulations and theories on maritime human resource management. The findings reveal that the Crewing Department plays a critical role in preventing undesirable incidents onboard, such as desertion, cargo theft, and operational failures. Such issues often originate from recruitment processes that fail to meet standard requirements or misalignments between crew perspectives and the company's vision and mission. PT Margo Indonesia Servicestama addresses these challenges by emphasizing integrity, professionalism, and adherence to company SOPs at every stage of crew procurement. The study concludes that the Crewing Department functions not only as a liaison between shore management and the ship’s crew but also as the primary filter responsible for maintaining high-quality human resources at sea. Continuous dedication, professionalism, and transparent procedures are recommended to sustain and improve fleet operational quality.